Customer relationship management (CRM) in healthcare organization: A review of ten years of research - Baashar Y.M.; Mahomood A.K.; Almomani M.A.; Alkawsi G.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Digital libraries; Health care; Information science; Sales; Customer relationship management; Google scholar; Healthcare organizations; Medline; Web of Science; Public relations